Kidney transplant patients with SARS‐CoV‐2 infection: The Brescia Renal COVID task force experience. Issue 11 (2nd August 2020) - Bossini, Nicola; Alberici, Federico; Delbarba, Elisa; Valerio, Francesca; Manenti, Chiara; Possenti, Stefano; Econimo, Laura; Maffei, Camilla; Pola, Alessandra; Terlizzi, Vincenzo; Salviani, Chiara; Moscato, Marianna; et al.
Abstract : The outcome of kidney transplant patients with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection is still unclear. Here we describe the clinical characteristics, disease outcome, and risk factors for acute respiratory distress syndrome (ARDS) and death of a cohort of 53 kidney transplant patients with coronavirus disease 2019 (COVID‐19). Eight of 53 have been handled as outpatients because of mild disease, on average with immunosuppression reduction and the addition of hydroxychloroquine and azithromycin; no patients required admission, developed ARDS, or died. Because of severe symptoms, 45/53 required admission: this cohort has been managed with immunosuppression withdrawal, methylprednisolone 16 mg/d, hydroxychloroquine, and antiviral drugs. Dexamethasone and tocilizumab were considered in case of ARDS. About 33% of the patients developed acute kidney injury, 60% ARDS, and 33% died. In this group, thrombocytopenia was associated to ARDS whereas lymphopenia at the baseline, higher D‐dimer, and lack of C‐reactive protein reduction were associated with risk of death. In the overall population, dyspnea was associated with the risk of ARDS and age older than 60 years and dyspnea were associated with the risk of death with only a trend toward an increased risk of death for patients on tacrolimus. In conclusion, SARS‐CoV‐2 infection may have a variable outcome in renal transplant patients, with higher risk of ARDS and death in the ones requiring admission. Abstract : Findings from an Italian cohort of kidney transplant patients with COVID‐19 support heterogenous disease courses with higher risks of acute respiratory distress syndrome and death in the subgroup with severe disease.